2016
DOI: 10.15171/ijpni.2016.06
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial, antioxidant and anti-inflammatory assessment of a phytocosmetic produced with glycinin peptides

Abstract: Phytocosmetics are increasingly gaining attention from consumers who search for alternatives for the maintenance and protection of the skin. This article reports formulation of a phytocosmetic derived from defatted soybean flour, an emulsion base that is hydrolyzed from the glycinin protein (1000 µg/g). Test for stability, microbiological control and biological activities antimicrobial (agar diffusion method), antioxidant (method of ABTS/TEAC radicals) and anti-inflammatory (method of hyaluronidase enzyme) pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…thermal stress, the results showed that the incorporation of the dry and glycolic extracts did not interfere with the stability of the emulsion in relation to this parameter. 15,18,20 The pH should ensure the stability of the formulation excipients, the efficacy and safety, as well as their compatibility with the biological fluids in accordance with the intended route of administration. The systems present greater stability when the pH values are kept within a small variation, which was visualized in the formulations studied.…”
Section: Discussionmentioning
confidence: 99%
“…thermal stress, the results showed that the incorporation of the dry and glycolic extracts did not interfere with the stability of the emulsion in relation to this parameter. 15,18,20 The pH should ensure the stability of the formulation excipients, the efficacy and safety, as well as their compatibility with the biological fluids in accordance with the intended route of administration. The systems present greater stability when the pH values are kept within a small variation, which was visualized in the formulations studied.…”
Section: Discussionmentioning
confidence: 99%
“…However, other proteins or peptides contained in LSE could be responsible for the observed effects against H. pylori. Thus, glycinins and β-conglycinins, predominant proteins in LSE (Table 1) could contribute on this activity since hydrolyzates from these proteins have been demonstrated to exert potent antimicrobial effects against E. coli [48]. The Kunitz-type trypsin and Bowman-Birk serine protease inhibitors, also identified in LSE, have been associated to antibacterial activity [49].…”
Section: Antimicrobial Activity Of Lse Against H Pylorimentioning
confidence: 99%
“…71 Hydrolysates of glycine and β-conglycinin from isolated soy protein can produce antioxidant and antimicrobial peptides as well. 72 In this regard, antimicrobial properties of soy protein isolates might contribute to the reduction of bacterial counts after soy consumption. 73 Further, it was proven that the oligosaccharides and water-soluble dietary fiber in soybeans decreased the in vitro formation of ammonia, indole, and phenol by fecal microbiota.…”
Section: ■ Protein Food Sourcesmentioning
confidence: 99%